Pemberdayaan Ekonomi Masyarakat Melalui Badan Usaha Milik Desa di Desa Wisata Lerep - Suwito, Ristiana; Yusuf, Amin (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2020)
The purpose of this research is to This study aims to describe the empowerment process and supporting factors and inhibiting factors in the economic empowerment of the community through BUMDES in Lerep Tourism Village. This study uses a descriptive qualitative approach, the method of data collection uses interviews, observation and documentation. The research subjects consisted of 2 BUMDES managers as key informants, 4 BUMDES members as additional informants. The data validity technique uses source triangulation and methods. The data analysis technique uses data collection, data reduction, data presentation, and conclusion / verification. The results of the study show that the empowerment process has 7 stages, namely: the preparation stage, the assessment of alternative planning programs or activities, the perfomalization of the action plan, the implementation of programs or activities, evaluation and termination; the drivers of empowerment are abundant natural resources, support from the community and the government, as well as the intentions and enthusiasm of empowered individuals. While the inhibiting factor is the lack of human resources who understand the BUMDES, the budget is still minimal, and the community lacks confidence in the importance of the BUMDES.